Calculus

posted by .

Consider the function f(x)=(7/x^2)-(6/x^6).
Let F(x) be the antiderivative of f(x) with F(1)=0.
Then F(2) equals _____.

  • Calculus -

    Write it as
    f(x) = 7x^-2 - 6x^-6
    F(x)= -7x^-1 + (6/5)x^-5 + c

    F(2) = -7/2 + (6/5)/2^5 + c
    = ......

  • Calculus -

    since F(1) = 0, we have
    -7 + 6/5 + c = 0

    which you can plug in to evaluate F(2)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Business Calculus

    The indefinite integral, or which call the "antiderivative", of f'(x)=6x-8x^3 is f(x) = 3x^2 - 2x^4 + C where C is any constant. Plug in x = 2 to that to see what C is. 3 = 3*4 - 2*16 + C Determine the antiderivative of the following …
  2. math

    Consider the function f(t)=2sec^2(t)–6t^2 . Let F(t) be the antiderivative of f(t) with F(0)=0 . Then F(5)=?
  3. Calculus

    What is the antiderivative of this? What is the antiderivative of x/((16+x^2)^(1/2))?
  4. Calculus

    Consider the function f(x)=x^4 + 8sqrtx Let F(x) be the antiderivative of f(x) with F(1)=-4. Then F(x)=_____
  5. Calculus I

    Consider the function f(x)=((2)/(x^2))-((3)/(x^5)). Let F(x) be the antiderivative of f(x) with F(1) = 0. Find F(3).
  6. Calculus (Antiderivatives)

    Suppose f(x) is a continuous function. Then a function F(x) such that F'(x) = f(x) is called: A.) the indefinite integral of f B.) the antiderivative of f C.) an antiderivative of f D.) a definite integral of f E.) All of the above
  7. calculus

    Consider the function f(x)=(x^3)(e^9x), -2 is less than or equal to x is less than or equal to 4 *The absolute maximum value is _____ and this occurs at x equals 4. *The absolute minimum value is _____ and this occurs at x equals ______ …
  8. Calculus

    Consider the function f(x)=(8)/(x^2)−(8)/(x^5) . Let F(x) be the antiderivative of f(x) with F(1)=0. Then F(2) equals ?
  9. calculus

    7) Consider the function f(x)=(10/x^2)−(2/x^6). Let F(x) be the antiderivative of f(x) with F(1)=0. Then F(x)= ?
  10. CALCULUS

    Consider the function f(x)=9x3−4x5. Let F(x) be the antiderivative of f(x) with F(1)=0. Then F(4) =

More Similar Questions